2017
DOI: 10.1038/onc.2017.105
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic lung cancer-secreted exosomal miR-23a increased angiogenesis and vascular permeability by targeting prolyl hydroxylase and tight junction protein ZO-1

Abstract: Hypoxia plays a critical role during the evolution of malignant cells and tumour microenvironment (TME).Tumour-derived exosomes contain informative microRNAs involved in the interaction of cancer and stromal cells, thus contributing to tissue remodelling of tumour microenvironment. This study aims to clarify how hypoxia affects tumour angiogenesis through exosomes shed from lung cancer cells. Lung cancer cells produce more exosomes under hypoxic conditions than do parental cells under normoxic conditions. miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
412
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(424 citation statements)
references
References 43 publications
10
412
1
1
Order By: Relevance
“…Inhibition of tumor angiogenesis has been speculated to be one of the most promising strategies to inhibit tumor growth and metastasis. However, traditional anti‐angiogenesis treatments sometimes lead to accelerated tumor growth by inducing hypoxia and metastasis . To use anti‐angiogenesis therapies effectively in CRC, it is essential to identify the molecular mechanisms that activate angiogenesis in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of tumor angiogenesis has been speculated to be one of the most promising strategies to inhibit tumor growth and metastasis. However, traditional anti‐angiogenesis treatments sometimes lead to accelerated tumor growth by inducing hypoxia and metastasis . To use anti‐angiogenesis therapies effectively in CRC, it is essential to identify the molecular mechanisms that activate angiogenesis in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that exosomal miRNA can modulate angiogenesis through targeting different mRNAs (van Balkom et al, ; Kang et al, ; Liang et al, ; Ramakrishnan et al, ). Exosomal miR‐126‐3p from CD34 + stem cells (Mathiyalagan et al, ), exosomal miR‐125a from adipose‐derived MSCs (Liang et al, ), exosomal miR‐23a from hypoxic lung cells (Hsu et al, ), exosomal miR‐17‐92 cluster and miR‐21 from leukaemia cells (Umezu et al, ), and exosomal miR‐21 from glioma stem cell (Sun et al, ) promote endothelial cell viability, proliferation, migration, or tube formation. Here, we showed that miR‐106b‐5p is down‐regulated in hCPFs‐Exo and this down‐regulation enhances endothelial cell angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Another report specified the role of miR‐27a/b from breast cancer cells with anti‐angiogenic properties (Hannafon et al, ) and another member from the cluster miR‐23a in Exosomes has been reported to act as a biomarker in colon cancer development (Ogata‐Kawata et al, ). Recently in 2017, Hsu et al () provided the evidence for the exosomal transfer of miR‐23a from hypoxic Lung cancer cells leading to increased angiogenesis by targeting prolyl hydroxylase and the tight junction protein ZO‐1. With convincing data on the role of horizontally transferred miR‐23a in the process of angiogenesis, we next tried to find the mechanism that may be responsible for miR‐23a mediated effect in angiogenic process.…”
Section: Discussionmentioning
confidence: 99%